Global value chains and tariffs: Insights from theory and model-based analysis - Victoria Havsteen Branner; Madeleine van Deurs (Danmarks Nationalbank, 2025)
Changing trade patterns, higher tariffs and increased geoeconomic fragmentation are increasingly shaping the global economy. It is important for Danmarks Nationalbank to have the tools to analyse and assess the consequences of these trends to ensure a robust Danish economy. This memo presents insights from theoretical trade literature and reviews the mechanisms captured by an advanced general equilibrium model used by Danmarks Nationalbank.
Keywords: 330; Globale Wertschöpfungskette; Zollpolitik; Geoökonomie; Internationale Wirtschaft; Welt